2013
DOI: 10.1007/s10661-013-3191-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of private economic benefits and positive environmental externalities of tea plantation in China

Abstract: Tea plantations are rapidly expanding in China and other countries in the tropical and subtropical zones, driven by relatively high private economic benefit. However, the impact of tea plantations on the regional environment, including ecosystem services and disservices are unclear. In this study, we developed an assessment framework for determining the private economic benefits and environmental externalities (the algebraic sum of the regulating services and disservices) of tea plantations in China. Our resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…There were two main reasons for this: First, it was hard to implement mechanization in the mountain regions with terraced shapes where most tea gardens were located. Second, the short harvesting period for tea leaves required a concentrated pulse of labor to pick leaves within the time of optimum maturity [3]. The second greatest economic cost of TEPM was planting trees and intercropping with peanuts or soybeans.…”
Section: Economic Analysis Of Tea Pest Management Modementioning
confidence: 99%
See 1 more Smart Citation
“…There were two main reasons for this: First, it was hard to implement mechanization in the mountain regions with terraced shapes where most tea gardens were located. Second, the short harvesting period for tea leaves required a concentrated pulse of labor to pick leaves within the time of optimum maturity [3]. The second greatest economic cost of TEPM was planting trees and intercropping with peanuts or soybeans.…”
Section: Economic Analysis Of Tea Pest Management Modementioning
confidence: 99%
“…The literature suggested that adopting a TEPM system with highly positive environmental and social externalities (public benefits) and private economic benefits would mitigate the trade-off between the short term economic benefits of increased tea production through the use of chemical pesticides and long-term losses of ecosystem services [3]. However, the long-term benefits regarding the use of TEPM were not included in the income estimation [4].…”
Section: Introductionmentioning
confidence: 99%
“…Tea is one of the three most common beverages (i.e., coffee, tea and cocoa) worldwide, and tea crops are widely planted in the tropical and subtropical regions (Xue et al, 2013). China is the world's largest tea-producing country, and its tea plantation area had reached 1.85 million ha in 2009, contributing approximately 52 % to the world total (Han et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…Tea (Camellia sinensis (L.) Kuntze), as a perennial cash crop, has been widely cultivated long-term in the tropical and subtropical regions of the word, with nearly 90% of the global tea harvest area currently located in Asia and over 50% of that located within China (http://www.fao.org/faostat/). To maximize the economic benefits, especially in China, tea production has expanded intensively, mostly through the conversion of arable uplands, rice paddies and forests into tea plantations (e.g., Xue et al, 2013;Yao et al, 2015). For instance, both the total harvest area and production have dramatically increased by 166% (from 1.09×10 6 to 2.90×10 6 ha) and 253% (from 6.8×10 5 to 2.40×10 6 Mg), respectively, from 2000 to 2016 (http://www.fao.org/faostat/).…”
Section: Introductionmentioning
confidence: 99%